Emotion regulation strategies and the two-dimensional model of adult attachment: a pilot study - Domic-Siede, Marcos; Guzmán-González, Mónica; Burgos, Josefa; Carvallo, Catalina; Flores-Guerra, Camila; Fredes-Valenzuela, Constanza; Suazo, Javiera; Véliz-García, Oscar; Calderón, Carlos; Sánchez-Corzo, Andrea; Perrone-Bertolotti, Marcela; Marín-Medina, Jennifer (Frontiers in Behavioral Neuroscience, 2023)
Emotion Regulation plays a crucial role in human's daily lives. Extensive research has shown that people with different attachment orientations exhibit divergencies in how they perform emotion regulation strategies. 44 adults performed an experimental emotion regulation task in which they were instructed to attend, reappraise, or suppress their emotions while viewing negative and neutral images taken from the International Affective Picture System (IAPS). Afterward, participants rated valence, arousal, and emotional dominance elicited by the images. Additionally, attachment orientations were measured using the ECR-12 questionnaire. Results showed a relationship between attachment avoidance and the level of arousal during the reappraisal condition; specifically, the higher attachment avoidance levels, the greater the emotional intensity during the implementation of cognitive reappraisal strategy. Such results suggest an association between failing in downregulate intense emotions using cognitive reappraisal when there are higher levels of attachment avoidance. Consistently, we also found that lower dominance during reappraisal was associated with more levels of avoidance. These results indicate that people with higher levels of attachment avoidance experience difficulties when using the cognitive reappraisal strategy to reduce the emotional impact produced by negative emotional stimuli. Our findings reinforce the idea that avoidant people experience high physiological activation when experience emotions.